St. Kitts and Nevis : Fifth and Sixth Reviews Under the Stand-By Arrangement, Request for Waiver of Nonobservance of Performance Criterion and Request for Waiver of Applicability; Staff Report; Press Release. (IMF Staff Country Reports; Country Report, 2014)
This paper discusses St. Kitts and Nevis' Fifth and Sixth Reviews under the Stand-By Arrangement (SBA), Request for Waiver of Nonobservance of Performance Criterion (PC) and Request for Waiver of Applicability. All fiscal program targets were met through the end of March 2013, partly thanks to strong receipts from the Citizenship by Investment program. However, the continuous PC on the nonaccumulation of government and guaranteed external arrears was missed by a minor amount because of temporary delays in payments. Three structural benchmarks were met at the end of December 2012 and the end of March 2013, while two benchmarks were met with delay. The IMF staff supports the authorities' request for the completion of the fifth and sixth reviews under the SBA and the waiver of applicability.